ANALISIS IMPLEMENTASI SISTEM PENJADWALAN ALAT BERAT PADA PT. PINDAD (PERSERO) - Sjamsuridjal; Nurul Rahmadini (JURNAL BISNIS dan TEKNOLOGI, 2024)
The research entitled "Analysis of the Implementation of the Heavy Equipment Scheduling System at PT. Pindad (Persero") was conducted on the demand for heavy equipment in order to produce appropriate and appropriate scheduling, so that product delivery to customers can be done on time. Based on the results of the research and discussion that have been carried out, it can be concluded that 1) The highest product sales in the make to order system are in the Pindad Dump Truck 24 M3 with an average product completion time ranging from one to seven days per unit. 2) The highest machine usage in the make to order system is in Overhead Crane and Mig Welding. 3) Based on the make to stock sales table with make to order, the make to stock system is superior. This difference occurs because of the availability of raw materials and the type of product. The highest machine usage in make to stock products is Overhead Crane, this is the same as the use of machines in make to order products. Keywords: heavy equipment scheduling, make to order, make to stock, PT. Pindad